Endoscopic management of superficial nonampullary duodenal tumors: European Society of Gastrointestinal Endoscopy (ESGE) Guideline - Vanbiervliet, Geoffroy; Moss, Alan; Arvanitakis, Marianna; Arnelo, Urban; Beyna, Torsten; Busch, Olivier; Deprez, Pierre H.; Kunovsky, Lumir; Larghi, Alberto; Manes, Gianpiero; Napoleon, Bertrand; Nalankilli, Kumanan; Nayar, Manu; Pérez-Cuadrado-Robles, Enrique; Seewald, Stefan; Strijker, Marin; Barthet, Marc; van Hooft, Jeanin E. (Endoscopy, 2021)
1 ESGE recommends that all duodenal adenomas should be considered for endoscopic resection as progression to invasive carcinoma is highly likely.Strong recommendation, low quality evidence.2 ESGE recommends performance of a colonoscopy, if that has not yet been done, in cases of duodenal adenoma.Strong recommendation, low quality evidence.3 ESGE recommends the use of the cap-assisted method when the location of the minor and/or major papilla and their relationship to a duodenal adenoma is not clearly established during forward-viewing endoscopy.Strong recommendation, moderate quality evidence.4 ESGE recommends the routine use of a side-viewing endoscope when a laterally spreading adenoma with extension to the minor and/or major papilla is suspected.Strong recommendation, low quality evidence.5 ESGE suggests cold snare polypectomy for small (< 6 mm in size) nonmalignant duodenal adenomas.Weak recommendation, low quality evidence.6 ESGE recommends endoscopic mucosal resection (EMR) as the first-line endoscopic resection technique for nonmalignant large nonampullary duodenal adenomas.Strong recommendation, moderate quality evidence.7 ESGE recommends that endoscopic submucosal dissection (ESD) for duodenal adenomas is an effective resection technique only in expert hands.Strong recommendation, low quality evidence.8 ESGE recommends using techniques that minimize adverse events such as immediate or delayed bleeding or perforation. These may include piecemeal resection, defect closure techniques, noncontact hemostasis, and other emerging techniques, and these should be considered on a case-by-case basis.Strong recommendation, low quality evidence.9 ESGE recommends endoscopic surveillance 3 months after the index treatment. In cases of no recurrence, a further follow-up endoscopy should be done 1 year later. Thereafter, surveillance intervals should be adapted to the lesion site, en bloc resection status, and initial histological result. Strong recommendation, low quality evidence.